NT5DC2 promotes tumorigenicity of glioma stem-like cells by upregulating fyn. (10th July 2019) - Guo, Saisai; Ran, Haowen; Xiao, Dake; Huang, Haohao; Mi, Lanjuan; Wang, Xinzheng; Chen, Lishu; Li, Da; Zhang, Songyang; Han, Qiuying; Zhou, Tao; Li, Ailing; et al.
Abstract: Glioblastoma (GBM) is an incurable primary brain tumor that is highly resistant to current treatments. Glioma stem-like cells (GSCs) are an aggressive population of glioma cells that not only initiate malignant growth, but also promote therapeutic resistance. Thus, targeting GSCs is critical for improving GBM treatment and ensuring complete eradication of the tumor. Here, we show that NT5DC2 (5′-Nucleotidase Domain Containing 2), a functionally unknown protein, plays a crucial role in GSC tumor initiation via upregulating Fyn expression. NT5DC2 is preferentially expressed in GSCs relative to the non-stem tumor cells. Knockdown of NT5DC2 significantly inhibits the GSC tumorsphere formation and cell viability in vitro, and tumorigenesis in vivo, thus, prolonging animal survival. Moreover, disruption of NT5DC2 in GSCs markedly reduces the expression of Fyn, a Src family proto-oncogene that has been implicated in the regulation of GBM progression. Importantly, the expression of NT5DC2 strongly correlated with increased aggression of human gliomas, but not that of other brain tumors. Taken together, our results uncover the function of NT5DC2 in GSC maintenance and highlight NT5DC2 as a promising therapeutic target for GBM. Highlights: NT5DC2 is preferentially expressed in glioma stem-like cells. NT5DC2 promotes glioma stem-like cells tumorigenesis. NT5DC2 up-regulates Fyn expression in glioma stem-like cells. NT5DC2 correlates with glioma malignant progression and patient survival.